The Zodiac Series: 10 Erotic Short Stories for Pisces - Löv, Nicole (Saga Egmont, 2024)
Part of an erotic star signs series from LUST, ‘The Zodiac Series: 10 Erotic Short Stories for Pisces’ is a collection of erotica that aligns with this water sign. Mythical and intuitive, these stories woven with fantasy are perfect for this fish sign to lose itself in the act of lovemaking. You dream of fairytale romance and seductive fantasies so let these stories seduce you into their cool and sensual waters.